Extent of palliative care need in the acute hospital setting: a prospective survey of two acute hospitals in the UK. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Gardiner, Clare; Ingleton, Christine; Gott, Merryn; Noble, Bill; Bennett, Mike; Seymour, Jane
Abstract : Background: The End of Life Care Strategy for England has highlighted the delivery of high quality palliative care in the acute hospital setting as an area of priority, acknowledging that a proportion of patients dying in hospitals receive poor care. The identification of patients who may benefit from palliative care is well recognised as problematic and health professionals have reported difficulties with recognising when a palliative care approach may be appropriate. Aim: To explore the extent of palliative care need in the acute hospital setting, and to explore agreement between different sources in the identification of patients with palliative care need. Method: A prospective survey of inpatients at two UK acute hospitals. Hospital case notes were examined for evidence of palliative care need according to GSF criteria. Ward based medical and nursing staff were asked to identify patients with palliative care needs according to a standardised definition. Results: Data were collected from 514 consenting patients (response rate 37.8%), of these185 (36.2%) met one or more GSF criteria for palliative care need. Medical staff identified 15.5% of patients as having palliative care needs, and nursing staff 17.4% of patients. Agreement between medical staff and GSF (κ=0.22), and nursing staff and GSF (κ=0.25) was poor in relation to identifying patients with palliative care needs. Conclusion: The results reveal that according to the GSF prognostic guide, over a third of hospital inpatients meet the criteria for palliative care need. Consensus between medical staff, nursing staff and the GSF was poor regarding the identification of patients with palliative care needs. This has significant implications for patient care and draws into question the utility of the GSF in the hospital setting. Further research should seek to develop standardised criteria for identifying patients with palliative care needs in hospital, and to educate staff in implementing guidelines.